2010
DOI: 10.1063/1.3483231
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of a passively mode-locked laser by continuous wave optical injection

Abstract: We investigate numerically and experimentally the properties of a passively mode locked quantum dot semiconductor laser under the influence of cw optical injection. We demonstrate that the waveform instability at high pumping for these devices can be overcome when one mode of the device is locked to the injected master laser and additionally show spectral narrowing and tunability. Experimental and numerical analyses demonstrate that the stable locking boundaries are similar to these obtained for optical inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…The data can be fitted well with the parabola showing the linear pulse chirp with instantaneous frequency of ν = dφ dt = 2at, with a = 0.62( rad s 2 ). The laser exhibited a double pulse shape above a gain current of 200 mA and no pulse shape recovery was possible for the free-running laser at higher currents, similar to [8].…”
Section: Free Running Qd-mllmentioning
confidence: 94%
See 1 more Smart Citation
“…The data can be fitted well with the parabola showing the linear pulse chirp with instantaneous frequency of ν = dφ dt = 2at, with a = 0.62( rad s 2 ). The laser exhibited a double pulse shape above a gain current of 200 mA and no pulse shape recovery was possible for the free-running laser at higher currents, similar to [8].…”
Section: Free Running Qd-mllmentioning
confidence: 94%
“…These regimes can potentially be exploited for high speed switching or data storage in optical networks. Recent experiments on optical injection locking of QD-MLLs have shown an improved control of the pulse train, chirp reduction, wavelength tuning, and pulse stabilization [7,8]. A number of theoretical studies revealed the bifurcation mechanisms responsible for phase locking of a MLL to an external master frequency and pulse repetition frequency locking of a hybrid MLL to external RF modulation [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, to optically injected single mode lasers, this can be implemented using injection locking from a single-mode laser, but here the slave laser emits a frequency comb instead of a single frequency. We have recently demonstrated both theoretically and experimentally that optical injection can inhibit waveform instabilities observed in quantum dot ML lasers and improve the time-bandwidth product of these lasers [3]. Also, experiments demonstrated that a two-frequency injection can, in addition, lead to a reduction of the ML pulse-timing jitter [4].…”
Section: Introductionmentioning
confidence: 97%
“…The basic idea is to determine if it is possible to control the soliton interaction through continuous external injection. Let us note that continuous optical injection has been used to efficiently stabilize a passively mode-locked quantum dot semiconductor laser [29,30]. Indeed, these lasers usually suffer from waveform instability at high pump power.…”
Section: Introductionmentioning
confidence: 99%